Annual implementation planning for systematic administration and school development. - Rathnapala, H.L.I.L. (My University, 1988)
The purpose of this study was to describe how principals of selected scondary school currently involve themselves in annual implementation planning for systematic routine administration and school development. In view of achieving this goal, the following six arears were selected to be studied in depth...